Mechanical and Pharmacological Revascularization Strategies for Prevention of Microvascular Dysfunction in ST-Segment Elevation Myocardial Infarction: Analysis from Index of Microcirculatory Resistance Registry Data. (9th July 2020) - Jang, Ji-Hun; Lee, Man-Jong; Ko, Kyu-Yong; Park, Jin-Hee; Baek, Yong-Soo; Sung-Woo, Kwon; Shin, Sung-Hee; Woo, Seong-Ill; Kim, Dae-Hyeok; Suh, Young Ju; Kwan, Jun; Park, Sang-Don
Abstract : Objectives . We aimed to identify mechanical and pharmacological revascularization strategies correlated with the index of microcirculatory resistance (IMR) in ST-elevation myocardial infarction (STEMI) patients. Background . Microvascular dysfunction (MVD) after STEMI is correlated with infarct size and poor long-term prognosis, and the IMR is a useful analytical method for the quantitative assessment of MVD. However, therapeutic strategies that can reliably reduce MVD remain uncertain. Methods . Patients with STEMI who underwent primary percutaneous coronary intervention (PCI) were enrolled. The IMR was measured with a pressure sensor/thermistor-tipped guidewire immediately after primary PCI. High IMR was defined as values ≥66 th percentile of IMR in enrolled patients (IMR > 30.9 IU). Results . A total of 160 STEMI patients were analyzed (high IMR = 54 patients). Clinical factors for Killip class P = 0.006, delayed hospitalization from symptom onset P = 0.004, peak troponin-I level P = 0.042, and multivessel disease P = 0.003 were associated with high IMR. Achieving final thrombolysis in myocardial infarction myocardial perfusion grade 3 tended to be associated with low IMR P = 0.119, whereas the presence of distal embolization was significantly associated with high IMR P = 0.034 . In terms of therapeutic strategies that involved adjusting clinical and angiographic factors associated with IMR, preloading of third-generation P2Y12 inhibitors correlated with reducing IMR value ( β = −10.30, P < 0.001 ). Mechanical therapeutic strategies including stent diameter/length, preballoon dilatation, direct stenting, and thrombectomy were not associated with low IMR value (all P > 0.05 ), and postballoon dilatation was associated with high IMR ( β = 8.30, P = 0.020 ). Conclusions . In our study, mechanical strategies were suboptimal in achieving myocardial salvage. Preloading of third-generation P2Y12 inhibitors revealed decreased IMR value, indicative of MVD prevention.